Factors influencing participation of a running community in virtual and physical running events - Villarico, Neil Daniel M. 2000-; Dimarucut, Alberto (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2023)
Running has become a popular recreational activity over the past years and this is evident in the increased participation in running events. However, when the pandemic hit sporting events were canceled, but some sports organizers were able to adapt their events into a virtual one, which was received with mixed opinions. This research aims to fill the gap in understanding runners in terms of the factors that influence their participation in physical and virtual running events. This utilized an online survey questionnaire that was posted in four running groups in social media with Filipino runners. The study found out that primary reasons for joining running events was for health and fitness, and for the challenge and motivation from the running events. It also unveiled that there is no significant relationship between the factors influencing participation and their run ' experience, except for the number of joined running events which have shown a significant association with running experience. Moreover, respondents showed slightly greater preference for physical running events, followed by a combination of both events in their future participation. Overall, the results suggest that participation in running events is on a personal needs level and physical running events are more preferred and these should be considered when crafting programs and future running events.
Vita
Thesis(Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Running races; Sports -- Psychological aspects